2021
DOI: 10.1155/2021/3928326
|View full text |Cite|
|
Sign up to set email alerts
|

Examining the Effectiveness of Using Adaptive AI-Enabled e-Learning during the Pandemic of COVID-19

Abstract: This study aimed to identify the effect of using adaptive AI-enabled e-learning on developing digital content creative design skills among postgraduate students. The research tools included an achievement test and an observation checklist for rating the practical performance. Research results concluded that, regardless of learning styles, the proposed adaptive e-learning environment had a positive effect on developing both cognitive achievement and practical performance of digital content creative design skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…One of them was to provide materials accessible to all learners [72,139]. Another way to manage the teachinglearning process is by making it self-paced, simulating real-life experiences, and improving collaboration under such difficult circumstances [18,68,75,101].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them was to provide materials accessible to all learners [72,139]. Another way to manage the teachinglearning process is by making it self-paced, simulating real-life experiences, and improving collaboration under such difficult circumstances [18,68,75,101].…”
Section: Discussionmentioning
confidence: 99%
“…Two relied on the application of Computer sciences [99] and Engineering [100] to explore the implementation of AI and machine learning in online higher education. Two publications examined the impact and effectiveness of AI-enabled elearning interaction in online learning during the pandemic in areas related to Education sciences [101], and also in no particular domain in higher education but rather a selection of students and instructors from different majors [102]. One paper focused on Business, Economics, and Administration in entrepreneurship education [103].…”
Section: Adaptive Learning Systems and Personalizationmentioning
confidence: 99%
“…In other words, instead of being static in their modeling, adaptive AI systems learn from new information and adjust their actions or predictions accordingly (e.g., Kumar & Kumar, 2018;Penttilä et al, 2019). In education, adaptive AI systems are expected to adjust and personalize educational content and experiences based on individual student needs, preferences, and performance (e.g., Younes, 2021). The primary goal is to provide a more tailored educational experience, for example, by ensuring that students receive the right content at the right pace, thereby enhancing learning processes.…”
Section: Adaptive Ai In Educationmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%